2016
DOI: 10.1002/ejic.201501436
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Lived, Emissive Excited States in Direct and Amide‐Linked Thienyl‐Substituted RuII Complexes

Abstract: Abstract:The excited state behavior of a new series of homoleptic and heteroleptic Ru II complexes bearing thienyl groups appended to a 2,2′-bipyridine chelating ligand via direct, secondary and tertiary amide linkages is examined. The results of nanosecond transient absorption spectroscopy, emission lifetime measurements and bimolecular quenching experiments are correlated to determine that although the amide linkage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
2
0
1
Order By: Relevance
“…These results strongly indicate that the accessibility of the planar structure over the aryl substituted dmp enhances the π-conjugation over the dmp ligand. The similar phenomena about the long excited-state lifetime caused by the planarity between aryl substituents and α-diimine ligand has been discussed for emissive Ru complexes, in which the delocalization of negative charge over the substituted bpy (bpy = 2,2′-bipyridine) in the 3 MLCT excited state lowers their structural changes from the ground state, leading to decreasing k nr (Damrauer et al, 1997; Majewski et al, 2016). It is also reported that the Cu I (dmp) complex has the close-lying 3 π-π * state near the lowest 3 MLCT excited state as for Cu I (dmp)(PPh 3 )2+, which showed the vibronic emission spectrum at 77 K as a long-lifetime component as τ em ~ 10 ms (Rader et al, 1981).…”
Section: Resultsmentioning
confidence: 56%
“…These results strongly indicate that the accessibility of the planar structure over the aryl substituted dmp enhances the π-conjugation over the dmp ligand. The similar phenomena about the long excited-state lifetime caused by the planarity between aryl substituents and α-diimine ligand has been discussed for emissive Ru complexes, in which the delocalization of negative charge over the substituted bpy (bpy = 2,2′-bipyridine) in the 3 MLCT excited state lowers their structural changes from the ground state, leading to decreasing k nr (Damrauer et al, 1997; Majewski et al, 2016). It is also reported that the Cu I (dmp) complex has the close-lying 3 π-π * state near the lowest 3 MLCT excited state as for Cu I (dmp)(PPh 3 )2+, which showed the vibronic emission spectrum at 77 K as a long-lifetime component as τ em ~ 10 ms (Rader et al, 1981).…”
Section: Resultsmentioning
confidence: 56%
“…Wolfs Gruppe interessiert sich für konjugierte Polymere und Materialien, die Photochemie und Photophysik von konjugierten Materialien und Koordinationskomplexen sowie die Synthese und den Einsatz modifizierter Nanomaterialien. Seine Veröffentlichung über das Verhalten von Ruthenium(II)‐Komplexen im angeregten Zustand wurde auf dem Titelbild des European Journal of Inorganic Chemistry vorgestellt …”
Section: Ausgezeichnet …unclassified
“…His report on the excited-state behavior of ruthenium-(II) complexes was featured on the cover of the European Journal of Inorganic Chemistry. [9] Curtis P. He has reported in Angewandte Chemie on interfacial halogen bonding. [10] Tom Woo (University of Ottawa) has been recognized with the CSC Tom Ziegler Award, which is given for contributions to computational and theoretical chemistry.…”
mentioning
confidence: 99%